Dynamics Simulation Analysis and Enhancement of Phased Array Antenna Plate. (April 2020) - Ye, Bin
Abstract: Phased array antennas have been widely used in military and civilian electronic fields as equipment for transmitting and receiving electromagnetic waves. The flatness of the antenna array is mainly ensured by the rigidity of the antenna frame. Therefore, the structural design of the planar array antenna mainly lies in the structural design of the antenna frame. Given the planarity requirements of the antenna array, how to properly design the structure of the antenna frame becomes a difficult problem facing the structural designer. In this paper, static stiffness and strength analysis are performed using finite element method(FEM) when the antenna is slipping. By establishing finit element model of the antenna, the platforms and the leatheroid ground, the laws of dynamic stress and deformation are researched. Analyse the reasons of structure breakage when it slips, and than advance the method of enhancing the stiffness and strength, offer a theoretical basis of structure design.